Desempenho e fitossensibilidade do capim mombaça (megathyrsus maximus) à aplicação de herbicidas - Oliveira, Álex Pereira (Universidade Federal do Tocantins, 2021)
The application of active principles with effect herbicides in pastures is considered one of the most effective weed control methods, however it must be taken into account that they can cause phytotoxicity to the established crop. The objective of this work was to evaluate the effect of the application of different active principles under pasture of Mombaça grass (Megathyrsus maximus cv. Mombaça). The active ingredients Triclopir, Fluroxipir, Picloram and the combination of 2.4D + Picloram were used. A completely randomized design was used with five treatments and four replicates each, totaling 20 experimental units. The evaluated variables were: total dry matter production, leaf dry mass, stem and dead material, leaf: stem ratio, percentage of total dry matter, leaf dry matter, stem and dead material and percentage of leaf blade, thatch and dead material. The percentage of leaf dry matter and dead material increased with the use of Triclopir, while for the other variables tested, no statistical differences were observed, showing selectivity of the active ingredients tested.